A SURVEY OF THE PERCEPTION OF QUANTITY SURVEYORS REGARDING TENDER-PRICE INDICES IN SOUTH AFRICA - J.H. CRUYWAGEN (Journal of Construction Project Management and Innovation)
Different indices are encountered in the building industry for use by built environment professionals, such as input-price indices, output-price indices and seller’s-price indices. Currently there is only one tender-price index (or output-price index) that is published on a regular basis in South Africa, through the University of Stellenbosch Bureau of Economic Research (BER) building cost index. This article is based on information gathered from two questionnaire surveys conducted among quantity surveyors in South Africa regarding their perception of tender-price indices (TPI) in South Africa. The research findings indicate that a TPI is an important tool for use by quantity surveying practices. One of the problems related to the accuracy of the BER index is the lack of information provided by quantity surveying practices. A suggested remedy for this problem can be the involvement of the ASAQS. There may be room for a new, alternative TPI, based on recent information, in the South African building industry.